Purification and characterization of two xylanases from alkalophilic and thermophilic Bacillus licheniformis 77-2 - Damiano, Valquiria B. [UNESP]; Ward, Richard; Gomes, Eleni [UNESP]; Alves-Prado, Heloiza Ferreira [UNESP]; Da Silva, Roberto [UNESP] (Humana Press Inc, 2006)
The alkalophilic bacteria Bacillus licheniformis 77-2 produces significant quantities of thermostable cellulase-free xylanases. The crude xylanase was purified to apparent homogeneity by gel filtration (G-75) and ionic exchange chromatography (carboxymethyl sephadex, Q sepharose, and Mono Q), resulting in the isolation of two xylanases. The molecular masses of the enzymes were estimated to be 17 kDa (X-I) and 40 kDa (X-II), as determined by SDS-PAGE. The K(m) and V(max) values were 1.8 mg/mL and 7.05 U/mg protein (X-I), and 1.05 mg/mL and 9.1 U/mg protein (X-II). The xylanases demonstrated optimum activity at pH 7.0 and 8.0-10.0 for xylanase X-I and X-II, respectively, and, retained more than 75% of hydrolytic activity up to pH 11.0. The purified enzymes were most active at 70 and 75 degrees C for X-I and X-II, respectively, and, retained more than 90% of hydrolytic activity after 1 h of heating at 50 degrees C and 60 degrees C for X-I and X-II, respectively. The predominant products of xylan hydrolysates indicated that these enzymes were endoxylanases.
Keywords: xylanase; Bacillus licheniformis; xylanase purification; alkalophilic bacteria; xylanase characterization